In vivo effect of two different pulsed electromagnetic field frequencies on osteoarthritis. Issue 5 (5th February 2014) - Veronesi, F.; Torricelli, P.; Giavaresi, G.; Sartori, M.; Cavani, F.; Setti, S.; Cadossi, M.; Ongaro, A.; Fini, M.
ABSTRACT Osteoarthritis (OA) is a joint pathology characterized by fibrillation, reduced cartilage thickness and subchondral bone sclerosis. There is evidence that pulsed electromagnetic fields (PEMFs) counteract OA progression, but the effect of two different PEMF frequencies has not yet been shown. The aim of this study was to test the effectiveness of PEMFs at two different frequencies (37 and 75 Hz) in a late OA stage in 21‐month‐old Guinea pigs. After 3 months of 6 h/day PEMF stimulation, histological and histomorphometric analyses of the knees were performed. At both frequencies, PEMFs significantly reduced histological cartilage score, fibrillation index (FI), subchondral bone thickness (SBT) and trabecular number (Tb.N) and increased trabecular thickness (Tb.Th) and separation (Tb.Sp) in comparison to the not treated SHAM group. However, PEMFs at 75 Hz produced significantly more beneficial effects on the histological score and FI than 37 Hz PEMFs. At 75 Hz, PEMFs counteracted cartilage thinning as demonstrated by a significantly higher cartilage thickness values than either those of the SHAM or 37 Hz PEMF‐treated groups. Although in severe OA both PEMF frequencies were able to limit its progression, 75 Hz PEMF stimulation achieved the better results. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:677–685, 2014.